Possible scenarios for single, double, or multiple kinetic freeze-out in high-energy collisions - Waqas, M; Liu, F-H; Fakhraddin, S; Rahim, M A (Indian journal of physics, 2019)
Transverse momentum spectra of different types of particles produced in mid-rapidity interval in central and peripheral gold–gold (Au–Au) collisions, central and peripheral deuteron–gold ( d –Au) collisions, and inelastic (INEL) or non-single-diffractive (NSD) proton–proton ( pp ) collisions at the Relativistic Heavy Ion Collider (RHIC), as well as in central and peripheral lead–lead (Pb–Pb) collisions, central and peripheral proton–lead ( p –Pb) collisions, and INEL or NSD pp collisions at the Large Hadron Collider (LHC) are analyzed by the blast-wave model with Boltzmann–Gibbs statistics. The model results are largely consist with the experimental data in special transverse momentum ranges measured by the PHENIX, STAR, ALICE, and CMS Collaborations. It is showed that the kinetic freeze-out temperature of emission source is dependent on particle mass, which reveals the scenario for multiple kinetic freeze-out in collisions at the RHIC and LHC. The scenario for single or double kinetic freeze-out is not observed in this study.